Accuracy of diagnostic imaging modalities for peripheral post-traumatic osteomyelitis – a systematic review of the recent literature - Govaert, Geertje A. (Eur J Nucl Med Mol Imaging, 2017)
AIMS: Post-traumatic osteomyelitis (PTO) is difficult to diagnose and there is no consensus on the best imaging strategy. The aim of this study is to present a systematic review of the recent literature on diagnostic imaging of PTO. METHODS: A literature search of the EMBASE and PubMed databases of the last 16 years (2000–2016) was performed. Studies that evaluated the accuracy of magnetic resonance imaging (MRI), three-phase bone scintigraphy (TPBS), white blood cell (WBC) or antigranulocyte antibody (AGA) scintigraphy, fluorodeoxyglucose positron emission tomography (FDG-PET) and plain computed tomography (CT) in diagnosing PTO were considered for inclusion. The review was conducted using the PRISMA statement and QUADAS-2 criteria. RESULTS: The literature search identified 3358 original records, of which 10 articles could be included in this review. Four of these studies had a comparative design which made it possible to report the results of, in total, 17 patient series. WBC (or AGA) scintigraphy and FDG-PET exhibit good accuracy for diagnosing PTO (sensitivity ranged from 50–100%, specificity ranged from 40–97% versus 83–100% and 51%–100%, respectively). The accuracy of both modalities improved when a hybrid imaging technique (SPECT/CT & FDG-PET/CT) was performed. For FDG-PET/CT, sensitivity ranged between 86 and 94% and specificity between 76 and 100%. For WBC scintigraphy + SPECT/CT, this is 100% and 89–97%, respectively. CONCLUSIONS: Based on the best available evidence of the last 16 years, both WBC (or AGA) scintigraphy combined with SPECT/CT or FDG-PET combined with CT have the best diagnostic accuracy for diagnosing peripheral PTO.